A New Hexa‐TiIV‐Substituted Sandwich‐Type Polyoxotungstate: Hydrothermal Synthesis, Structure, and Oxidative Decontamination of Chemical Warfare Agent Simulant. Issue 5 (23rd January 2020) - Wang, Yue‐Lin; Sun, Jun‐Jun; Qin, Dan; Yang, Guo‐Yu
Abstract : A new hexa‐Ti IV ‐substituted sandwich‐type silicotungstate, Na2 (H2 enMe)4 [Ti6 (µ‐O)9 (A‐α‐SiW9 O34 H2 )2 ]· 16H2 O (1, enMe = 1, 2‐diaminopropane) has been synthesized under mild hydrothermal conditions and characterized by FT‐IR spectroscopy, elemental analysis, thermogravimetric analysis, single‐crystal and powder X‐ray diffraction. Compound 1 contains a dimeric polyoxoanion with two [A‐α‐SiW9 O34 ] 10– Keggin moieties sandwiching a trigonal‐prismatic [Ti6 (µ‐O9 )] 6+ cluster. The catalytic performance of 1 was evaluated for the oxidative decontamination of chemical warfare agent, i.e. sulfur mustard simulant, 2‐chloroethyl ethyl sulfide (CEES), using H2 O2 under ambient conditions, showing that 1 is an excellent catalyst for the rapid and complete transformation from CEES to nontoxic 2‐chloroethyl ethyl sulfoxide (CEESO) with 100 % selectivity. In addition, 1 exhibits good stability and recyclability. Abstract : A new hexa‐Ti IV ‐substituted sandwich‐type silicotungstate, Na2 (H2 enMe)4 [Ti6 (µ‐O)9 (A‐α‐SiW9 O34 H2 )2 ]· 16H2 O, was made under mild hydrothermal conditions. It exhibits excellent catalytic activity and selectivity for the oxidative decontamination of sulfur mustard simulant.